Aspects of Mathematical Modeling of Complex Processes Realized in Combined Onboard Systems - Abramov, V. V.; Kuptsov, I. M.; Yablochnikov, S. L.; Bukhensky, K. V. (Systems of Signals Generating and Processing in the Field of on Board Communications (Online), 2024)
The aspects of mathematical modeling of the dynamics of complex processes in complex onboard systems are considered. The structural connections between the elements of modeled systems and their dynamics are formalized using a system of differential equations. Qualitative analysis of the synthesized model allowed establishing new non-local conditions for stable functioning of modeled combined onboard systems. The results obtained make it possible to expand the working areas of technical devices and the devices included in onboard systems.